Early and prolonged oral edaravone for neuroprotection in acute ischemic stroke: the ERASE-STROKE randomized controlled phase 3 trial - Yang Xiang; Wang-Sheng Jin; Xin-Chen Zhu; Yan Song; Xiao Chen; Qing-Hua Wang; Hao-Lun Sun; Yang Zhao; Xiao-Rong Yu; Tao Feng; Ai-Hong Guo; Hong-Guo Dai; et al. (Science Bulletin, 2026)

17β-estradiol reshapes the reproductive dose–response to polystyrene nanoplastics in the rotifer Brachionus calyciflorus - Qi-bin Zhu; Yi-fan Feng; Yi-fu Xing; Yu Zhang; Jiang-hua Yang; Cui Han; Xiao-jie Liu; Jia-xin Yang (Aquatic Toxicology, 2026)

Chemical composition of the endogenous fungus Fusarium sp. L-3 derived from Chinese Qinan agarwood - Ming-Li Han; Qing-Yun Ma; Li Yang; Qing-Yi Xie; Jiao-Cen Guo; Hao-Fu Dai; Na Xiao; You-Xing Zhao (Natural Product Research, 2026)

Virulensome: a transient organelle mediating fungal virulence - Pei-Ji Zhao; Qian-Yi Hu; Si-Han Wang; Cheng-Song Wang; Xue-Xian Jian; Xing-Fu Wen; Yu-Lin Luo; Ya-Qi Zhang; Chun-Mei Xiang; Guo-Hong Li; Shu-Qun Liu; Ming-He Mo; et al. (Science China Life Sciences, 2026)

Polystyrene nanoplastics disrupt iron homeostasis by promoting FPN1 ubiquitination in GC-2spd(ts) cells - Xinru Cui; Yitong Shang; Liyang Ding; Zhen Zhang; Yu Deng; Tengjiao He; Bo Xu; Xufeng Fu; Xing Du; Hang Han (Toxicology, 2026)

Precision measurement of the Ds*+-Ds+ meson mass difference - M. Ablikim; M.N. Achasov; P. Adlarson; X.C. Ai; R. Aliberti; A. Amoroso; Q. An; Y. Bai; O. Bakina; Y. Ban; H.-R. Bao; V. Batozskaya; et al. (Science Bulletin, 2026)

A multilevel regression model to explain disparities in residential cooling infrastructure across heat-threatened regions - Yang Yang; Haoying Han; Shuyang Li; Jiayi Fu; Xing Su; Chao Fan (Applied Geography, 2026)

The interplay between antihypertensive medication and lifestyle with cardiovascular outcomes in patients with hypertension: the PURE-China study - Biyan Wang; Zhiguang Liu; Tong Bu; Sumathy Rangarajan; Qiuyan Ma; Xiaocong Li; Qi Qiu; Yang Lin; Lap Ah Tse; Bo Hu; Salim Yusuf; Qiujing Cai; et al. (EPMA Journal, 2026)

First evidence of CP violation in beauty baryon to charmonium decays - R. Aaij; A.S.W. Abdelmotteleb; C. Abellan Beteta; F. Abudinén; T. Ackernley; A.A. Adefisoye; B. Adeva; M. Adinolfi; P. Adlarson; C. Agapopoulou; C.A. Aidala; Z. Ajaltouni; et al. (Science Bulletin, 2026)

Manganese cycle-mediated synchronous bacteria-algae/anammox coupled denitrification system under low-temperature conditions: Performance and mechanisms - Peng-fei Yu; Dian-lin Jiang; Ding Wang; Xing-guan Ma; Jun-Li; Li-yao Han; Ao Wang; Yu-bo Fu; Xing Jin (Bioresource Technology, 2026)

Few-shot natural frequency prediction of Camellia oleifera for vibration harvesting enabled by synthetic data generation - Feng Liu; Dongying Mo; Han Fu; Shaozheng Yu; Xuan Chu; Nan She; Xing Xu; Weizu Wang; Jieli Duan (Computers and Electronics in Agriculture, 2026)

Fabrication of Prussian blue mixed matrix membranes based on the synchronous growth for water treatment - Xiaotong Lu; Xing Gao; Xiaojiao Hou; Bingbing Chen; Peining Han; Tieqiang Wang; Fanbao Meng; Yu Fu (Chemical Engineering Journal, 2026)

Combining untargeted metabolomics and chemometrics to reveal the metabolic profiles of jujube-hawthorn fermented beverages at different fermentation stages - Zhibin Xing; Tarun Belwal; Hao Huang; Xiang Li; Liangxia Han; Yahui Yin; Chunhui Shan; Xizhe Fu; Yinglin Du (Food Chemistry, 2025)

The recovery mechanism of granular sludge fragmentation and re-granulation caused by long-term high-concentration organic matter erosion in the SAD process: performance, sludge evolution, and metagenomic sequencing - Peng-fei Yu; Ding Wang; Yu-bo Fu; Xing-guan Ma; Hao Zheng; Li-yao Han; Ao Wang; Dian-lin Jiang; Hai-wen Sun; Xing Jin (Bioresource Technology, 2025)

The influence of water flow disturbance form on the granulation of algae sludge: Granulation property, treatment effect and algae biological structure - Peng-fei Yu; Ao Wang; Hai-wen Sun; Ding Wang; Xing-guan Ma; Yu-jia Wang; Bo-mei Hu; Li-yao Han; Yu-bo Fu; Dian-lin Jiang; Shi-gang Tu (Journal of Water Process Engineering, 2025)

Discovery of dietary beneficial compounds for healthy aging: From worm to human - Xianjiang Ye; Hao Wang; Yuxuan Han; Xing Fu; Jiuliang Zhang; Tao Zhang (Food Research International, 2025)

System characteristics of integrated continuous flow simultaneous partial Nitrification, Anammox and Denitrification (SNAD) for NH4+-rich wastewater: performance, sludge evolution, metagenomic sequencing analysis - Peng-fei Yu; Ding Wang; Xing-guan Ma; Yu-bo Fu; Li-yao Han; Ao Wang; Dian-lin Jiang; Hai-wen Sun; Dong-xue Li; Xing Jin; Kang-da Yang; Li-cheng Zhang; et al. (Environmental Research, 2025)

Nitrite and sulfide stress induces hepatopancreatic oxidative stress, lipid metabolism disorders, ferroptosis and apoptosis in the Chinese mitten crab, Eriocheir sinensis - Yi-Fu Xing; Yi-Fan Feng; Jian Tian; Qi-Bin Zhu; Cui Han; Xiao-Jie Liu; Jiang-Hua Yang; Jia-Xin Yang (Aquaculture, 2025)

Measurement of the decay Ξ 0 → Λ γ with entangled Ξ 0 Ξ ¯ 0 pairs - M. Ablikim; M.N. Achasov; P. Adlarson; O. Afedulidis; X.C. Ai; R. Aliberti; A. Amoroso; Q. An; Y. Bai; O. Bakina; I. Balossino; Y. Ban; et al. (Science Bulletin, 2025)

Nitrite and sulfide stress affects physiological and metabolic functions of gills in crab Eriocheir sinensis - Yi-fu Xing; Yi-fan Feng; Jian Tian; Yu Zhang; Cui Han; Xiao-jie Liu; Jia-xin Yang (Aquaculture, 2025)

Single-cell omics: experimental workflow, data analyses and applications - Fengying Sun; Haoyan Li; Dongqing Sun; Shaliu Fu; Lei Gu; Xin Shao; Qinqin Wang; Xin Dong; Bin Duan; Feiyang Xing; Jun Wu; Minmin Xiao; et al. (Science China Life Sciences, 2025)

PM2.5-mediated cardiovascular disease in aging: Cardiometabolic risks, molecular mechanisms and potential interventions - Francis Chanda; Kai-xuan Lin; Abdallah Iddy Chaurembo; Jian-yuan Huang; Hui-juan Zhang; Wen-hui Deng; Yun-jing Xu; Yuan Li; Li-dan Fu; Hao-dong Cui; Chi Shu; Yang Chen; et al. (Science of The Total Environment, 2024)

Integrated transcriptomic and metabolomic analysis reveals the underlying mechanisms for male reproductive toxicity of polystyrene nanoplastics in mouse spermatocyte-derived GC-2spd(ts) cells - Hang Han; Zhen Zhang; Bo Xu; Liyang Ding; Hong Yang; Tiantian He; Xing Du; Xiuying Pei; Xufeng Fu (Toxicology in Vitro, 2024)

Stereo visual-inertial localization algorithm for orchard robots based on point-line features - Xing Xu; Jinming Liang; Jianying Li; Guang Wu; Jieli Duan; Mohui Jin; Han Fu (Computers and Electronics in Agriculture, 2024)

Ecotoxicological assessment, oxidative response, and enzyme activity disorder of the rotifer Brachionus asplanchnoidis exposed to a toxic cocktail of spent lithium-ion battery leachate - Yi-fan Feng; Yu Zhang; Run-jia Yang; Si-qi Li; Xiao-jie Liu; Cui Han; Yi-fu Xing; Jia-xin Yang (Journal of Hazardous Materials, 2024)

Upward soil arching effect under unloading: mechanism, theory and engineering application - Ren-Peng Chen; Han-Lin Wang; Xiang-Shen Fu; Fanyan Meng; Qi-Wei Liu; Xing-Tao Lin (Transportation Geotechnics, 2024)

Nrf2-mediated ferroptosis of spermatogenic cells involved in male reproductive toxicity induced by polystyrene nanoplastics in mice - Xufeng Fu; Hang Han; Hong Yang; Bo Xu; Wenjie Dai; Ling Liu; Tiantian He; Xing Du; Xiuying Pei (Journal of Zhejiang University-SCIENCE B, 2024)

Mechanical interlocking induced emission in two-dimensional covalent organic frameworks - Ruo-Meng Zhu; Wang-Kang Han; Yong Liu; Jia-Xing Fu; Jing-Dong Feng; Jinfang Zhang; Huan Pang; Zhi-Guo Gu (Chemical Engineering Journal, 2024)

Precise classification and regional delineation of maturity groups in soybean cultivars across China - Wenwen Song; Luping Liu; Shi Sun; Tingting Wu; Haiyan Zeng; Shiyan Tian; Bincheng Sun; Wenbin Li; Lijun Liu; Shuming Wang; Han Xing; Xin’an Zhou; et al. (European Journal of Agronomy, 2023)

Telomere length, oxidative stress and their links with growth and survival in a lizard facing climate warming - Qiong Zhang; Xing-Zhi Han; Pablo Burraco; Xin Hao; Li-Wei Teng; Zhen-Sheng Liu; Fu-Shun Zhang; Wei-Guo Du (Science of The Total Environment, 2023)

Effect of boron and nitrogen modulation in metal atoms anchoring on flower-like carbon superstructure for efficient ammonia electrosynthesis - Yanchao Zhao; Shuo Zhang; Cong Han; Qian Lu; Qiuju Fu; Huimin Jiang; Lingzhi Yang; Yanlong Xing; Qiuju Zheng; Jianxing Shen; Liting Yan; Xuebo Zhao (Chemical Engineering Journal, 2023)

Biomarkers of aging - Hainan Bao; Jiani Cao; Mengting Chen; Min Chen; Wei Chen; Xiao Chen; Yanhao Chen; Yu Chen; Yutian Chen; Zhiyang Chen; Jagadish K. Chhetri; Yingjie Ding; et al. (Science China Life Sciences, 2023)

Mechanical deterioration effect and damage evolution characteristics of soft sandstone with different water-immersed heights under uniaxial compression - Han-Dong Liu; Shuai Liu; Hai-Ning Liu; Jia-Xing Chen; Zhi-Guo Xia; Ju-Yun Zhai; Yun-You Fu (Bulletin of Engineering Geology and the Environment, 2023)

Involvement of Opioid Peptides in the Analgesic Effect of Spinal Cord Stimulation in a Rat Model of Neuropathic Pain - Fu-Jun Zhai; Song-Ping Han; Tian-Jia Song; Ran Huo; Xing-Yu Lan; Rong Zhang; Ji-Sheng Han (Neuroscience Bulletin, 2022)

A novel anticancer property of Lycium barbarum polysaccharide in triggering ferroptosis of breast cancer cells - Xing Du; Jingjing Zhang; Ling Liu; Bo Xu; Hang Han; Wenjie Dai; Xiuying Pei; Xufeng Fu; Shaozhang Hou (Journal of Zhejiang University-SCIENCE B, 2022)

Neuroprotective effect of aldose reductase knockout in a mouse model of spinal cord injury involves NF-κB pathway - Fu-xin Han; Rui Zhang; Xin-xing Yang; Shan-bo Ma; Shi-jie Hu; Bing Li (Experimental Brain Research, 2022)

Molecular identification and phylogenetic analysis of fungal pathogens isolated from diseased fish in Xinjiang, China - Yan‐Zhen Zhang; Qing‐Dian Han; Long‐Wei Fu; Yong‐Xing Wang; Zhi‐Hai Sui; Yun‐Guo Liu (Journal of Fish Biology, 2021)
The outbreaks of fungal diseases in cultured fish have been severe in recent years, which is harmful to the healthy and sustainable development of fish farming. In this study, an investigation was conducted for significant fungal infections of 12 species of fish in four regions in Xinjiang, China, to understand the distribution of local fish fungal pathogens. Twenty‐six fungal strains with pathogenicity were isolated, and the challenge experiment showed that eight strains from Changji area had high infection rate to fish eggs. Based on internal transcribed spacer sequence data and molecular analysis, the 26 strains were classified into nine different species of six fungal genera. Phylogenetic analysis showed that all strains were divided into two clades, namely Cluster 1 (contains only the genus Mucor ) and Cluster 2 (consists of five small branches), and the distribution of strains from the same region was scattered in two clusters. There is no strict host selectivity for these fungi to infect fish. Mucor sp. are the main fungal pathogen of fish in these four regions, whereas Hypophthalmichthys molitrix and Carassius auratus are two types of fish that were susceptible to pathogen. In addition, the environmental adaptability experiments showed that eight highly pathogenic strains have different adaptability to the environment, and their optimum temperature and pH were 25°C and 7.0, respectively, whereas the concentration of NaCl was negatively correlated with the growth of strains. Therefore, these results indicated that the coinfection of multiple fungal pathogens in a culture region should be considered in the future study.

A proteomic analysis of Bcl-2 regulation of cell cycle arrest: insight into the mechanisms - Xing Du; Jingjing Xiao; Xufeng Fu; Bo Xu; Hang Han; Yin Wang; Xiuying Pei (Journal of Zhejiang University-SCIENCE B, 2021)

A reciprocal egg-swap experiment reveals sources of variation in developmental success among populations of a desert lizard - Xin Hao; Chen-Xu Wang; Xing-Zhi Han; Yang Wang; Qiong Zhang; Fu-Shun Zhang; Bao-Jun Sun; Wei-Guo Du (Oecologia, 2021)

Quantitatively determine the dominant driving factors of the spatial—temporal changes of vegetation NPP in the Hengduan Mountain area during 2000–2015 - Shu-ting Chen; Bing Guo; Rui Zhang; Wen-qian Zang; Cui-xia Wei; Hong-wei Wu; Xiao Yang; Xiao-yan Zhen; Xing Li; Da-fu Zhang; Bao-min Han; Hai-ling Zhang (Journal of Mountain Science, 2021)

SNP of AHSA2 gene in three cattle breeds using snapshot technology - Shu-Zhu Cheng; E. Guang-Xin; Cheng-Li Liu; Wang-Dui Basang; Yan-Bin Zhu; Ri-Su Na; Yan-Guo Han; Yan Zeng; Xiao Wang; Wei-Wei Ni; Bai-Gao Yang; Xing-Hai Duan; et al. (Journal of Genetics, 2020)

Effects of different treatments on genes related to polysaccharide content in Dendrobium huoshanense - Jun Dai; Xing-bang Han; Nai-fu Chen; Cun-wu Chen; Nai-dong Chen; Xiang-wen Song; Xue-ping Jiang; Yu-juan Wang (Brazilian Journal of Botany, 2020)

Identification and evaluation of tobacco cytoplasmic male sterile line Nta(gla)S K326 generated from asymmetric protoplast fusion of Nicotiana glauca and N. tabacum followed by backcrossing with N. tabacum K326 - Xue-Jun Chen; Zhi-Jun Tong; Bing-Guang Xiao; Yong-Ping Li; Fang-Chan Jiao; Yong Li; Tao Pang; Dun-Huang Fang; Xing-Fu Wu; Yi-Han Zhang; He Xie; Ge Bai; et al. (Plant Cell, Tissue and Organ Culture (PCTOC), 2020)

Responses of Primary Afferent Fibers to Acupuncture-Like Peripheral Stimulation at Different Frequencies: Characterization by Single-Unit Recording in Rats - Ran Huo; Song-Ping Han; Feng-Yu Liu; Xiao-Jing Shou; Ling-Yu Liu; Tian-Jia Song; Fu-Jun Zhai; Rong Zhang; Guo-Gang Xing; Ji-Sheng Han (Neuroscience Bulletin, 2020)

Soil bacteria and fungi respond differently to plant diversity and plant family composition during the secondary succession of abandoned farmland on the Loess Plateau, China - Zekun Zhong; Xinyi Zhang; Xing Wang; Shuyue Fu; Shaojun Wu; Xuqiao Lu; Chengjie Ren; Xinhui Han; Gaihe Yang (Plant and Soil, 2020)

Joint 3D traveltime calculation based on fast marching method and wavefront construction - Hui Sun; Jian-Guo Sun; Zhang-Qing Sun; Fu-Xing Han; Zhi-Qiang Liu; Ming-Chen Liu; Zheng-Hui Gao; Xiu-Lin Shi (Applied Geophysics, 2017)

The heterogeneity of islet autoantibodies and the progression of islet failure in type 1 diabetic patients - Jin Liu; Lingling Bian; Li Ji; Yang Chen; Heng Chen; Yong Gu; Bingqin Ma; Wei Gu; Xinyu Xu; Yun Shi; Jian Wang; Dalong Zhu; et al. (Science China Life Sciences, 2016)

The influence of sea water velocity variation on seismic traveltimes, ray paths, and amplitude - Fu-Xing Han; Jian-Guo Sun; Kun Wang (Applied Geophysics, 2012)

Malignant transformation of 293 cells induced by ectopic expression of human Nanog - Yan-Li Lin; Zheng-Bin Han; Fu-Yin Xiong; Li-Yuan Tian; Xiao-Jie Wu; Shi-Wei Xue; Yan-Rong Zhou; Ji-Xian Deng; Hong-Xing Chen (Molecular and Cellular Biochemistry, 2011)

Carbon and nitrogen storage in plant and soil as related to nitrogen and water amendment in a temperate steppe of northern China - Fu-Mei Lü; Xiao-Tao Lü; Wei Liu; Xu Han; Guang-Ming Zhang; De-Liang Kong; Xing-Guo Han (Biology and Fertility of Soils, 2011)

Endemic Seed Plant Species from Hainan Island: A Checklist - Javier Francisco-Ortega; Fa-Guo Wang; Zhong-Sheng Wang; Fu-Wu Xing; Hong Liu; Han Xu; Wei-Xiang Xu; Yi-Bo Luo; Xi-Qiang Song; Stephan Gale; David E. Boufford; Mike Maunder; et al. (The Botanical Review, 2010)

Seed Plant Endemism on Hainan Island: A Framework for Conservation Actions - Javier Francisco-Ortega; Zhong-Sheng Wang; Fa-Guo Wang; Fu-Wu Xing; Hong Liu; Han Xu; Wei-Xiang Xu; Yi-Bo Luo; Xi-Qiang Song; Stephan Gale; David E. Boufford; Mike Maunder; et al. (The Botanical Review, 2010)

A new cytotoxic iridoid from Callicarpa nudiflora - Wen-Li Mei; Zhuang Han; Hai-Bin Cui; You-Xing Zhao; Yuan-Yuan Deng; Hao-Fu Dai (Natural Product Research, 2010)

Identification and characterization of piggyBac-like elements in the genome of domesticated silkworm, Bombyx mori - Han-Fu Xu; Qing-You Xia; Chun Liu; Ting-Cai Cheng; Ping Zhao; Jun Duan; Xing-Fu Zha; Shi-Ping Liu (Molecular Genetics and Genomics, 2006)

Salicylic Acid Enhances Jaceosidin and Syringin Production in Cell Cultures of Saussurea medusa - Zhen-Zhen Yu; Chun-Xiang Fu; Ying-Shan Han; Yong-Xing Li; De-Xiu Zhao (Biotechnology Letters, 2006)